Baamboozle's Effectiveness in Increasing Learning Motivation in Islamic Studies - Winaningsih, Elis Tuti; Syarif, F; Pahrurroji, Pahrurroji (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2022)
In the course of education in Indonesia, 2020 was a year full of challenges due to the emergence of the COVID-19 pandemic. Almost all schools in the world are closing classrooms and moving to virtual (online) classrooms. This is a big challenge for teachers, so teachers must find ways to make learning run effectively and efficiently, one way is by gamification. This study aims to explore and analyze the effectiveness of gamification in learning through the Bamboozle platform in increasing Islamic Studies learning motivation conducted on fifth-grade students at SD Islam Sinar Cendekia, South Tangerang. This research uses qualitative research (field research) and uses descriptive analysis methods with sociological and psychological approaches. Sources of research were obtained from the results of interviews with related parties, documentation collection, observation, and triangulation. Data analysis used the theory of Milles and Huberman. The results of the interviews showed that 20 student informants stated that learning activities made the spirit increase because it was fun, not boring, biased to reflect on the material, fun, and happy. This is reinforced by the results of interviews with parents and teachers as well as observations, so it can be concluded that bamboozling is one of the extrinsic factors that can increase students' learning motivation.